The Power of Proximity: Strategic Decisions in African Party Politics - Alexander Stroh (German Institute of Global and Area Studies (GIGA), 2009)
Recent publications suggest that exclusively ethnoregional parties are as rare in sub-Saharan Africa as elsewhere. At the same time, the idea that ethnicity is a very special feature of African party politics persists. The paper acknowledges the general relevance of ethnicity in party competition but emphasizes the level on which it becomes important. It develops a microbehavioral approach which pays particular attention to the strategic choices of party elites in order to supplement the dominant structuralist thinking in party research on Africa. An in-depth evaluation of detailed election data from Burkina Faso shows that strategies which rely on personal proximity between the voter and the candidates influence the parties' success to a great extent. Parties maximize their chances of winning seats if they concentrate their limited resources on the home localities of leading party members. Hence, African party politics are less dependent on ethnic demography than is often implied but more open to change through elite behavior. – – Die neuere Literatur legt nahe, dass exklusive ethnoregionale Parteien im subsaharischen Afrika ähnlich selten sind wie andernorts. Zugleich besteht die Vorstellung fort, dass Ethnizität für afrikanische Parteiensysteme besonders wichtig sei. Dieser Beitrag stellt deshalb nicht die grundsätzliche Bedeutung von Ethnizität im Parteienwettbewerb in Frage, sondern widmet sich der spezifischen gesellschaftlichen Ebene, auf der Ethnizität wichtig wird. Der hier entwickelte mikrobehaviorale Ansatz, der strategischen Entscheidungen von Parteieliten besondere Beachtung schenkt, soll die vorherrschende strukturalistische Herangehensweise der Parteienforschung zu Afrika ergänzen. Eine exemplarische Untersuchung detaillierter Wahldaten aus Burkina Faso zeigt, dass Strategien, die auf der persönlichen Nähe zwischen Wähler und Kandidat aufbauen, den Parteierfolg stark beeinflussen. Parteien maximieren ihre Wahlchancen, wenn sie ihre begrenzten Ressourcen auf die Heimatorte führender Parteimitglieder konzentrieren. Infolgedessen ist der afrikanische Parteienwettbewerb weit weniger an die ethnische Demographie gebunden als häufig unterstellt wird, sondern durch Elitenverhalten wandlungsfähig.
Keywords: 300; political parties; Burkina Faso; elections; local mobilization; resource efficiency; son of the soil